POSISI DAN PERANAN STRATEGIS PENGAJARAN IPA (FISIKA) DI SLTP - Mundilarto, Mundilarto (Jurnal Cakrawala Pendidikan, 2016)
It is felt that the availability ofhigh quality human resources has become an urgent need inrelation to the challenges that would be faced by the Indonesian nation in times to come. Thejuniorhigh school is a part ofthe nine-year basic school ing which is the required minimum education for all Indonesians. Therefore, the position and role ofthe teaching ofthe physical sciences there in the course of developing human resources is extremely strategic. For a number ofits graduates, the juniorhigh school is the last part oftheir formal education. After graduating, they generally choose working rather thari continuing their school ing. Meanwhile, a part ofthose who can continue their schooling may enter the field of the social sciences, a field which is no longer related to the physical sciences. In relation with the mission that the junior high school bears, the basic knowledge and skills students learn there should be flexibly useful for both future work and further study. Therefore, the teaching ofthe physical sciences at junior high school should be c.onducted accordingly efficiently and effectively.